DOPAMINE NEURON GLUTAMATE COTRANSMISSION: FREQUENCY-DEPENDENT MODULATION IN THE MESOVENTROMEDIAL PROJECTION - Chuhma, Nao (2009)
Mesoventromedial dopamine neurons projecting from the medial ventral tegmental area to the ventromedial shell of the nucleus accumbens play a role in attributing incentive salience to environmental stimuli that predict important events, and appear to be particularly sensitive to the effects of psychostimulant drugs. Despite the observation that these dopamine neurons make up almost the entire complement of neurons in the projection, stimulating their cell bodies evokes a fast glutamatergic response in accumbens neurons. This is apparently due to dopamine neuron glutamate cotransmission, suggested by the extensive coexpression of vesicular glutamate transporter 2 (VGLUT2) in the neurons. To examine the interplay between the dopamine and glutamate signals, we used acute quasi-horizontal brain slices made from DAT-YFP mice in which the intact mesoventromedial projection can be visualized. Under current clamp, when dopamine neurons were stimulated repeatedly, dopamine neuron glutamate transmission showed dopamine-mediated facilitation, solely at higher, burst-firing frequencies. Facilitation was diminished under voltage clamp and flipped to inhibition by intracellular Cs(+) or GDPβS, indicating that it was mediated postsynaptically. Postsynaptic facilitation was D1 mediated, required activation of NMDA receptors and closure of voltage gated K(+)-channels. When postsynaptic facilitation was blocked, D2-mediated presynaptic inhibition became apparent. These counterbalanced pre- and postsynaptic actions determine the frequency dependence of dopamine modulation; at lower firing frequencies dopamine modulation is not apparent, while at burst firing frequency postsynaptic facilitation dominates and dopamine becomes facilitatory. Dopamine neuron glutamate cotransmission may play an important role in encoding the incentive salience value of conditioned stimuli that activate goal-directed behaviors, and may be an important subtract for enduring drug-seeking behaviors.